The crispy popis / Amir Hassan Shamsul Ezam ...[et al.] - Shamsul Ezam, Amir Hassan; Zainal, Mohamad Asyraf; Habri, Adam; Reduan, Muhammad Aqil Fahmy; Ahmad Hashni, Aiman Haziq (2023)
The Crispy Popis offers popis product for customers, providing a variety of toppings such as caramel,chocolate,oreo and lotus biscoff to give high satisfaction to the consumers. The Crispy Popis marketing strategy is to emphasize the quality and price of our products. We offer the affordable price because many people in Bandar Baru Uda Johor Bahru are from middle to low class. Thus, we develop marketing strategy that gives attraction for our targeted customer to buy from us. The management of The Crispy Popis consists of 5 workers who are Amir Hassan, Muhammad Asyraf, Adam, Aqil Fahmy and Aiman Haziq. Our workers has extensive experience in finance, businesses, sales and accounting. Partners will take role responsibilities together instead of different duties and portfolio of partners. Based on our observations, our product which is popis is one of people’s favourite especially teenagers who love trendy and sweet food. People can easily be attracted to our product just with the presentation itself which are full of toppings such as chocolate, cheese, caramel, nestum and many more to choose. The crispy popis textures added with the sweet taste of the toppings will melt the heart of the consumers. For the future prospect, we hope that our partnerships business will expand bigger from time to time.